Coming Full Circle: New Ruralism. (May 2017) - Garber, Richard
Abstract : Particularly in areas of Africa and Asia, efforts are being made to accommodate new economic development without obliterating the rural way of life. Termed 'New Ruralism', the approach involves architects cooperating closely with local communities, ensuring that projects respect their cultural heritage and empowering them to actively participate in shaping their environment. The process is as important as the form in driving sustainability. Guest‐EditorRichard Garber explains the principles and illustrates them with a project in China by his own firm GRO Architects, and one in Kenya by his former employers SHoP Architects.